Analysis of Financial Management in Micro, Small and Medium Enterprises (MSMEs) in Takalar Regency - Hervina, Hervina; Suarni, Agusdiwana; Darwin, Khadija (Jurnal Ekonomi Balance, 2023)
This study discusses financial management in Micro, Small and Medium Enterprises (MSMEs) in Takalar Regency. The main problem of this research is that SMEs do not really understand about good financial management. Where there are 4 (four) indicators in financial management, namely financial planning, recording, reporting, and control. This study aims to find out how the application of financial management is carried out by MSME actors in Takalar Regency. This type of research uses a qualitative research type, with research locations in Takalar Regency. Data collection methods used are observation, interviews and document review. Informants in this study were 10 (ten) MSME’s engaged in the trading sector. The results of this study indicate that MSME actors in Takalar Regency have implemented financial management but have not maximized it. The most widely applied indicators are financial planning, recording and control. Meanwhile, reporting indicators have not been implemented properly. This is due to limited time and human resources and business actors running their own businesses. In addition, MSME’s do not have an accounting background so that knowledge related to financial management is still lacking.